Circulating Rotavirus Genotypes among Children Younger than 5 Years with Acute Gastroenteritis in Zaria, Northwestern Nigeria - Giwa, Fatima Jummai; Garba, Maria; Mukhtar, Abdulaziz; Idris, Mukhtar; Lartey, Belinda; Damanka, Susan; Samaila, Modupeola; Muktar, Hassan; Olayinka, Adebola; Armah, George (Journal of Pediatric Infectious Diseases, 2021)
Objective This study aimed to determine the circulating rotavirus genotypes among children 0 to 59 months with acute gastroenteritis in Zaria, Northwestern Nigeria.Methods A cross-sectional hospital-based study was performed from November 2015 to April 2017 on 415 stool samples of children 0 to 59 months with acute gastroenteritis presenting at the pediatric clinics in five selected health care facilities in Zaria, Northwestern Nigeria. The stool samples were tested for group A rotavirus antigen by enzyme-linked immunosorbent assay (ELISA) using the ProSpecT™ Rotavirus Microplate Assay (Thermo Scientific Oxoid, United Kingdom). Rotavirus-positive strains were further characterized using seminested multiplex reverse transcriptase polymerase chain reaction.Results Of the 415 diarrheal stool samples collected from children with acute gastroenteritis, 12.3% (n = 51) tested positive by ELISA. Five rotavirus G genotypes (G1, G2, G3, G9, and G12) and three P genotypes (P[4], P[6], and P[8]) were detected. Eight genotype combinations were detected with G1P[8], G12P[8], and G3P[6] being the most prevalent (9.8% each) followed by G1P[6], G2P[4], and G9P[8] (5.9% each). G/P mix types representing 25.5% (n = 13) of strains were detected during the study period.Conclusion This study found a high diversity of rotavirus strains with emerging unusual rotavirus genotypes and a concurrent high proportion of mixed infections. This increased antigenic diversity of rotavirus strains may impact on vaccine effectiveness and rotavirus epidemiology and highlights the importance of continuous surveillance.
Keywords: circulating; rotavirus; genotypes; children; Zaria; Northwestern Nigeria